Application-Based Digital Support for Labor Pain Across Cervical Dilatation: A Rapid Scoping Review and Evidence-Informed Design Framework - Irfana Tri Wijayanti; Luluk Yuliati (Proceeding Cendekia International Conference Health and Technology, 2026)
Abstract. Application-based non-pharmacological support is increasingly used during childbirth, yet its effects on labor pain are frequently conflated with effects on cervical progress. This rapid scoping review mapped patient-facing digital applications for labor-pain support, examined how intervention delivery related to cervical dilatation, and derived requirements for an intrapartum mobile-health application. PubMed/MEDLINE, Europe PMC, and OpenAlex were searched for empirical reports published from January 2015 to 26 July 2026. Eligibility followed a Population-Concept-Context framework, and reporting was guided by JBI methodology, PRISMA-ScR, and PRISMA-S. Thirty-three reports representing 31 unique studies or development programs were included. Immersive virtual reality dominated the evidence and generally reduced pain during or immediately after exposure; anxiety, fear, comfort, and satisfaction also commonly improved. Cervical dilatation was primarily used to determine eligibility, time intervention sessions, or standardize pain measurement. No study validated an increase in cervical dilatation rate, and findings for labor duration were inconsistent. An evidence-informed application should therefore make pain coping its primary claim, use clinically confirmed stage information, offer calming audio, affirmation, paced breathing, and mindfulness, support offline one-tap use and partner-midwife integration, and remain separate from clinical labor-progress monitoring.